“Eu vou, mas eu volto!”: procedimentos documentais aplicados ao Acervo Catalendas - LOBATO, Stephanie Lins Campos (2019)
The present work deals with the routes for the documentation of part of the Collection Catalendas. This collection presents a language of puppet theater, and is composed of dolls, scenarios and accessories of various types. These subjects were made from 1998 to 2013, by the group “In Bust” Theater With Dolls, for the production of the Program “Catalendas”, an accomplishment of TV Culture of Pará. The disciplines of curriculum were presented like part of the programming of the curricular exhibition "I go, But I will be back! The “Catalendas” and the Amazonian imaginary on TV" organized by the students of the UFPA museology course, from the group of 2015. For the documentation of the collection, a list of cataloging and a cataloging record was drawn up, using the documents used in the museum's documentation and the specificities of a collection of theatrical figures. Following the application of the factsheets, it seems necessary to draw up a classification plan.